Exports of Manufactures and Economic Growth : The Fallacy of Composition Revisited - Cline, William R. (World Bank, Washington, DC, 2017)
The author's 1982 article on the fallacy of composition questioned the feasibility of generalizing the "G4" (Hong Kong (China), the Republic of Korea, Singapore, and Taiwan (China)) growth model based on rapid growth of exports, on grounds that if all developing economies pursued it, their combined manufactured exports would eventually trigger protection in industrial countries. The1984 book of author identified a safe speed limit of about 10-15 percent annually for growth of developing country exports of manufactures, well below the 25-35 percent rate of Korea and Taiwan, China in the 1960s and 1970s. This study revisits this question in the light of a quarter-century of experience. It finds that developing countries' aggregate manufactured exports grew at about 10 percent annually, a robust pace but within the speed limits he had envisioned. Even so, in key sectors such as apparel, import penetration levels have exceeded thresholds that his earlier estimates would have suggested would provoke protection, suggesting the importance of increased World Trade Organization (WTO) discipline. The base of manufactured exports from poor countries remains small relative to that of China and the original G4, so there should be considerable room for export growth from these newcomers. However, a new macroeconomic version of the fallacy of composition problem could arise: the growing tendency of China and some other major emerging market economies to pursue rapidly rising trade surpluses that have their counterpart in an increasingly unsustainable U.S. current account deficit.